The phonemic, semantic and syntactic of Properties for Yaa Alnassab: An analytical descriptive study - Balkhair, Ahmed Abdullrahman (Al-Adab Journal, 2021)
The phenomenon of proportion is classified within the syntactic morphological phenomena; This is because the form of the attributed to him is done by attaching the Y of the noun at the end of the name in order to reach the meaning of the lineage, and this creates a syntactic case that has two parts in the total, one of them: It includes the formal aspects, i.e. the morphological phonemes that are concerned with describing the j of the ratios the accentuated phoneme at the abstract phonemic level first and then the syllabary level Some of the phonemic sequences surrounding this yaa within the context in which they are found. As for the second part, it is represented in the semantic and syntactic aspects of Yaa Nassab, which in turn includes the semantic and morphological function of the formula and the contextual function as well for this morphological suffix. The action of the verb, therefore, it was necessary to research the components of the work of the noun attributed to the action of the verb, with different opinions about all of that and discussion.